Salmonella spp. risk assessment for cooking of blade tenderized prime rib - Wendelburg, J.W.; Lambert, D.L.; Thippareddi, H.; Kastner, Curtis L.; Phebus, Randall K.; Marsden, James L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Prime rib is generally prepared by cooking to low temperatures for long times to attain the desired tenderness and juiciness. Destruction of Salmonella spp. in blade tenderized prime rib was examined by following cooking procedures commonly used by chefs. Beef ribs (boneless) were inoculated with Salmonella spp. to attain initial surface levels of about 5.75 log10 CFU/cm2. The ribs were blade tenderized (one pass) using a Ross blade tenderizer. Each was split into two equal sections. One half was cooked to a target internal temperature of 110 and the other half to 120°F, then tempered at room temperature for up to 60 min and placed in a holding oven (120°F) for up to 120 min. Reductions of 4.54 and 4.80 log10 CFU/g were attained for roasts removed from the oven at 110 and 120°F, respectively. Even though prime rib preparation utilizes very low cooked product temperatures, the long cooking time and tempering period result in substantial process lethality and a safe final product.
Keywords: Beef; Blade tenderization; Salmonella; Prime rib cookery